CHARACTERIZATION OF SOME MORPHOLOGY, ANATOMY AND PHYSIOLOGY OF THE WHEAT MUTANT (Triticum aestivum L.) DEWATA AND SELAYAR IN TROPICAL LOWLAND. - Laela Sari; Agus Purwito; Didy Sopandie (Widyariset, 2015)
Wheat mutant characterization is a part of the breeding programs to investigate the diversity that can influence in production increased. The  aim of this research was to obtain data characterization morphology, anatomy and physiology that could be used as selection criteria and obtain an adaptive wheat mutant in the tropical lowland area. The research was conducted in Seameo-Biotrop Experimental Garden, located on ±250 m above the sea level, from April until November 2013. There were 18 Dewata wheat mutants and two Selayar wheat mutants, which is an M3 derivative resulted from EMS treatment, were used. LC50 Dewata got the 0.3% EMS treatment for 30 minutes, while LC50 Selayar got the 0.1% EMS treatment for 60 minutes. The data analysis used Augmented Designs Method. The results showed that the mutant Dewata that was significantly affected the morphology was indicated by four characters i.e. cooking time (two mutants), grain weight per genotype (seven mutants), leaf area (five mutants), and green leaves (one mutant). There are two characters in mutant Selayar that bring significant influence on morphological factors, those are seed weight per genotype (one mutant) and leaf area (one mutant), while the cooking time and green leaves have no real effect. Anatomical character appearance on leaf thickness and the size of stomata showed different levels of tolerance between Dewata plant mutant (DW-0,3.30-2-13-3), Selayar mutant (SL-0,1.60-2-14-2), and its both controls. As for the physiological character, there were significant differences in the amount of proline and glucose levels. Proline level in Dewata control was 79.29 µg/gBB, while in DW mutant -0,3.30-2-13-3 was 332.37 µg/gBB. Proline levels in Selayar control was 201.53 µg/gBB, while in mutant SL mutant-0,1.60-2-14-2 was 335.79µg/gBB. Likewise, glucose level in Dewata control was 14.32mg/gBB, while in DW mutant 0,3.30-1-15-1 was 29.06 mg/gBB, Selayar controls (5.87 mg /GBB) with SL mutant-0,1.60-2-14-2 (17.68 mg /gBB).